IMPLEMENTASI ALGORITMA BLOWFISH UNTUK PENGAMANAN DATA PADA APLIKASI PENGELOLAAN KELOMPOK TANI DI KECAMATAN DAWUAN - Fahlevvi, Mohammad Rezza; Septiandi Harhari, Nurfadhilah; Ariandi, Wahyu (LPPM Universitas Putera Batam, 2025)
The rapid development of technology has increased the need for robust data security, especially in public administration managing sensitive information. This research aims to design a farmer group management application for Dawuan District, integrating the Blowfish algorithm to secure member data. The study employs the Rational Unified Process (RUP) methodology, comprising problem identification, system design, implementation, and evaluation stages. Blowfish, chosen for its speed and efficiency, encrypts critical information such as identification numbers, addresses, and contact details. System functionality and security tests confirm the algorithm’s effectiveness, demonstrating faster encryption times and reliable protection against data breaches compared to AES and 3DES. User feedback highlights the system’s practicality and alignment with local administrative needs. However, the study notes limitations in computational resource requirements and key management. Future research may explore performance optimization, blockchain integration for layered security, and mobile app development to enhance accessibility. This research contributes to the literature on cryptographic applications in public systems, presenting a scalable solution to secure farmer data and supporting regional efforts to comply with data protection regulations.